Democratic Temperament The Legacy of William James - Miller, Joshua (Book collections on Project MUSE., 1997)
This first book by a political theorist devoted exclusively to James's theory argues that political concerns were in fact central to his intellectual work. Joshua Miller links James to the contemporary public dialogue by treating him as a theorist of action and exploring the complexities of that theory. He also relates the philosopher's thought to his own political experiences and observations and - by explicating, criticizing, and meditating on James - develops provocative new ideas about issues facing democracy today.